“I Bring My Country into the Classroom”: Transposed identity negotiation among international teaching assistants in U.S. college writing programs - Scholastika Massawe; Carolyn Peterson (Journal of International Students, 2026)
International teaching assistants (ITAs) are central to U.S. higher education, yet their teaching has often been framed through concerns about language proficiency, accent, and classroom intelligibility. This collaborative ethnographic study examines how ITAs in U.S. college writing classrooms negotiate identity, legitimacy, and affect within sociopolitical teaching spaces. Drawing on transnationalism, transposed identity negotiation, critical pedagogy, and affective theory, we analyze classroom observations, fieldnotes, interviews, and researcher dialogues with five ITAs over one academic year. The findings show that ITAs’ authority is not grounded in native-like language proficiency but in relational presence, reflexive self-awareness, and ethical engagement. Participants transformed multilingualism, cultural experience, vulnerability, and emotional labor into pedagogical resources, using their transnational identities to build dialogue, care, and critical inquiry. The study challenges deficit framings of ITAs as linguistic apprentices and instead positions them as co-constructors of knowledge whose teaching reshapes writing classrooms as relational and transnational spaces.